2022
DOI: 10.1177/02841851221118476
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning reconstruction allows for usage of contrast agent of lower concentration for coronary CTA than filtered back projection and hybrid iterative reconstruction

Abstract: Background The demand for homogeneous and higher vascular contrast enhancement is critical to provide an appropriate interpretation of abnormal vascular findings in coronary computed tomography angiography (CTA). Purpose To evaluate the effect of various contrast media concentrations (Iohexol-370, Iohexol-300, Iohexol-240) and image reconstructions (filtered back projection [FBP], hybrid iterative reconstruction [IR], and deep learning reconstruction [DLR]) on coronary CTA. Material and Methods A total of 63 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Only 2 papers have used the same vendor as the one we used (Canon Medical Systems). [ 31 , 32 ] A possible explanation for this apparent disagreement with the results between all published papers could be the type of vendor used, with its specific DLR algorithm. In the DLR, the quality of the training target determines the performance of the output.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Only 2 papers have used the same vendor as the one we used (Canon Medical Systems). [ 31 , 32 ] A possible explanation for this apparent disagreement with the results between all published papers could be the type of vendor used, with its specific DLR algorithm. In the DLR, the quality of the training target determines the performance of the output.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study on coronary CTA [ 32 ] with the same vendor as our study investigated the influence of 3 different image reconstructions (FBR, hybrid IR, and DLR) with different contrast media iodine concentrations (Iohexol 370, Iohexol-300, Iohexol 240). They found that using DLR with the lowest concentration (Iohexol 240) yielded comparable attenuation to hybrid IR with Iohexol 300, with a higher SNR, CNR, and image quality for DLR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning reconstruction (DLR) [ 10 ] based on convolutional neural networks (CNNs) was proposed to further enhance the spatial resolution and diagnostic performance without affecting the noise texture. Previous studies demonstrated the benefits of DLR on coronary CT angiography [ 11 12 13 14 ], abdominal contrast-enhanced dual-energy CT [ 15 ], and brain CTA [ 16 ]. Here, we have extended the application of the DLR algorithm to dark-blood CTA to evaluate vessel wall imaging in the head and neck region.…”
Section: Introductionmentioning
confidence: 99%